Industrial sites (Scottish Historical and Archaeological Internet Reports, 2010)
The former estate brick and tile works at Smeaton and the engine house associated with Fuffet coal pit were archaeologically investigated. The features are described along with aims and methodology employed. There is a section on historical background and a summary of the associated artefacts.